Genetic population structure of the Asian longhorned tick, Haemaphysalis longicornis, in Japan - Morii, Kiyohito; Sakamoto, Yoshiko; Watari, Yuya; Iijima, Hayato; Doi, Kandai; Morishima, Kaori; Komine, Hirotaka; Okabe, Kimiko; Goka, Koichi (Experimental & applied acarology, 2025)
The Asian longhorned tick, Haemaphysalis longicornis Neumann (Ixodida: Ixodidae), is widely distributed across temperate East Asia, including Japan, and carries a variety of zoonotic diseases. The species includes bisexual and parthenogenetic lineages. Various aspects of these two lineages, such as their abundance ratio, genetic relationship, and population structure, remain unknown in island environments such as Japan that are isolated from the mainland. Therefore, in this study, 235 individuals were collected across 15 prefectures, and their mtDNA was analyzed to better understand the genetic population structure of this species in Japan. Haplotype analysis of the 631 bp cox 1 region revealed the presence of 38 haplotypes, which showed for the first time that a large diversity of haplotypes is present in Japan. In addition, the calculated haplotype diversity was 0.889—equivalent to that reported in the study that examined haplotypes across a larger region in China. This indicates that Japan is a hotspot of genetic diversity of this species. The haplotype network of this species was divided into two major clades, but there were no clear geographical boundaries in the distributions of the haplotypes. However, a qualitative cline was observed in the distribution of sexual lineage, with the parthenogenetic lineage being more prevalent in northeastern Japan and the bisexual lineage being more prevalent in southwestern Japan. Future analysis combining the results of this paper with information from nuclear DNA and large-scale mtDNA analyses would facilitate a more detailed understanding of the population structure and historical distributions of the Asian longhorned tick.